Alteration of chondroitin sulfate composition on proteoglycan produced by Knock-in mouse embryonic fibroblasts whose versican lacks the A subdomain - Keittisak Suwan (2018)
Versican/PG-M (proteoglycan-mesenchymal) is a large chondroitin sulfate (CS) proteoglycan of the extracellular matrix (ECM) that is constitutively expressed in adult tissues such as dermis and blood vessels. It serves as a structural macromolecule of the ECM, while in embryonic tissue it is transiently expressed at high levels and regulates cell adhesion, migration, proliferation, and differentiation. Knock-in mouse embryonic (Cspg2Δ3/Δ3) fibroblasts whose versican lack the A subdomain of the G1 domain exhibit low proliferation rates and acquire senescence. It was suspected that chondroitin sulfate on versican core protein would be altered when the A subdomain was disrupted, so fibroblasts were made from homozygous Cspg2Δ3/Δ3mouse embryos to investigate the hypothesis. Analysis of the resulting versican deposition demonstrated that the total versican deposited in the Cspg2Δ3/Δ3fibroblasts culture was approximately 50% of that of the wild type (WT), while the versican deposited in the ECM of Cspg2Δ3/Δ3fibroblasts culture was 35% of that of the WT, demonstrating the lower capacity of mutant (Cspg2D3/D3) versican deposited in the ECM. The analysis of CS expression in the Cspg2Δ3/Δ3fibroblasts culture compared with wild-type fibroblasts showed that the composition of the non-sulfate chondroitin sulfate isomer on the versican core protein increased in the cell layer but decreased in the culture medium. Interestingly, chondroitin sulfate E isomer was found in the culture medium. The amount of CS in the Cspg2Δ3/Δ3cell layer of fibroblasts with mutant versican was dramatically decreased, contrasted to the amount in the culture medium, which increased. It was concluded that the disruption of the A subdomain of the versican molecule leads to lowering of the amount of versican deposited in the ECM and the alteration of the composition and content of CS on the versican molecule.